COMPARISON BETWEEN SAP FLOW MEASUREMENTS AND TWO PREDICTION CLIMATE FORMULAS TO ESTIMATE TRANSPIRATION IN OLIVE ORCHARDS (OLEA EUROPAEA L. CV. CHEMLALI) - Amani, Bchir; Olfa, Boussadia; Raoul, Lemeur; Mohamed, Braham (European Scientific Journal, ESJ, 2013)
An experimental study was carried out on irrigated olive trees (cv. Chemlali) growing in the arid climate of Gafsa (Tunisia), aiming to estimate the irrigation water requirements of olive trees for a possible optimization of irrigation. To achieve this objective, sap flow was estimated for whole trees using the heat dissipation method. Transpiration (T) was estimated by the Penman-Monteith and Priestley-Taylor formulas. Results shows that sap flow depends essentially on solar radiation (with R2=0.857). This study showed a good correlation between the xylem sap flow and climatic parameters (air temperature, solar radiation, vapor pressure deficit). We also found a good regression between sap flow measured by the heat dissipation method and transpiration calculated by Penman-Monteith equation (PM) (R2=0.886) and by Priestley-Taylor equation (R2=0.883).